Postural control in children with down syndrome: Evaluation of functional balance and mobility - Leite, Jessica Cristina; Neves, Jessica Caroliny De Jesus; Vitor, Leonardo George Victorio; Fujisawa, Dirce Shizuko [UNESP] (FapUNIFESP (SciELO), 2018)
The delay in motor development in children with Down Syndrome (DS), as a consequence of the characteristics and presence of associated disorders, may lead to slowness in the acquisition or limitations of functional abilities. Thus, this study aims to characterize the balance and functional mobility of children with DS, since they enable the execution of daily activities. The cross-sectional study with sample convenience was performed with children with DS, confirmed through karyotype, between the ages of 8 and 12 years old. The evaluation of postural control was performed with two instruments: Pediatric Balance Scale (PBS) and Reach Test (RT). Twenty-one participants with DS, 12 (57%) boys and nine (43%) girls, median age of 10 [8-11] years old, were evaluated. The score obtained in the PBS was 53 (51-54). The distance obtained in the RT was 19 cm (17-23.5). The results showed that the performance of functional activities was little affected, according to the median of the score in the PBS; however, some participants scored between 48 to 51. The measurements obtained in the RT imply a reduction in functional mobility.
Controle postural em crianças com síndrome de down: Avaliação do equilíbrio e da mobilidade funcional
Keywords: Child development; Down syndrome; Physical therapy; Special education